Determination of Cadmium and Lead in farmed fish tissues and feed in Khartoum State – Sudan - Ahmed, Aied Berer Musa; elnasri, hind Abdealaziz (Food, Agriculture and Natural Resources - NETWORKS, 2023)
Heavy metals are known for their toxic effects and lead to serious health problems. Fish is widely consumed, and the fish industry is rapidly growing. Heavy metals can accumulate in different parts of the fish from water, feed or sediment and can be further transferred to human consumers. The objective of the current study was to determine the concentrations of Cd and Pb in farmed fish tissues and fish feed. Fish tissues (head and fins, muscle and gills) in addition to feed samples were collected from two fish farms in Khartoum State. The levels of Cd and Pb were measured in the samples using Atomic Absorbance technique. Cd and Pb were detected in all samples examined, but their levels were below the acceptable limits set by FAO/WHO and EU. The muscle tissue was found to have the lowest concentration of both minerals (Cd 0.0092±0.001mg/g and Pb 0.203 ± 0.01 mg/g respectively) and the highest concentration was found in the fins (Cd 0.017± 0.001 and Pb 0.263 ± 0.011 mg/g respectively) .The levels in the feed were also found to be below the acceptable limits. Cd and Pb were detected in all samples studied, although the levels were below acceptable limits. Albeit that, the continuous and regular measurement is important to determine any potential sources that can increase their levels which further can affect the health of fish and humans.